A comparison of progestogens or oral contraceptives and gonadotropin-releasing hormone agonists for the treatment of endometriosis: a systematic review. (April 2014) - Jeng, Cherng-Jye; Chuang, Linus; Shen, Jenta
<x xml:space="preserve">Abstract</x> Objective: This systematic review examined the use of progestogens or oral contraceptives and gonadotropin-releasing hormone (GnRH) agonists for the treatment of endometriosis. Research design and methods: Inclusion criteria were: i) randomized controlled trials (RCTs); ii) comparison of progestogens with GnRH agonists for treatment of endometriosis; and iii) endometriosis diagnosed by laparoscopy or laparotomy. Main outcome measures: Pelvic pain, bone mineral density, serum estradiol level, and side effects. Results: Of 128 articles identified, there were four RCTs comparing the use of progestogens and GnRH agonists. In three studies a progestogen (gestrinone, lynestrenol, or dienogest) was compared with leuprolide. In one study, ethinyl estradiol/norethindrone was compared with leuprolide/norethindrone. A meta-analysis was not possible as the studies varied markedly in their protocols, inclusion criteria, and the drugs and doses administered. Leuprolide was as effective as gestrinone, dienogest, and continuous oral contraceptives (OCs) for the relief of endometriosis-related pain, whereas it was superior to lynestrenol. Leuprolide was associated with a significant reduction in bone mineral density and estradiol levels and a higher incidence of hot flushes, headaches, mood changes, and vaginal dryness, whereas progestogens were associated with higher incidences of weight gain and acne. Conclusions: These results suggest that progestogens or OCs may be used as first-line therapy for endometriosis.